PROBLEMATIKA NELAYAN SEBAGAI SUMBER IDE DALAM PENCIPTAAN KARYA SENI LUKIS - Rizki Maulana; Syamsiar - Syamsiar (Texture:Art and Culture Journal, 2022)
The creation of the Final Project entitled "The Problem of Fishermen as a Source of Ideas in the Creation of Paintings" is motivated by personal experience in the environment around the house related to the problems faced by fishermen in Brebes Regency. The author describes the expression of concern and hope for fishermen about the importance of welfare for fishermen and understands the problems that have an impact on the fishermen's environment. The process of making this Final Project uses the Herman Von Helmholtz method, including the saturation stage, namely the collection of facts, data and sensations, then the incubation stage, namely the deposition stage and the last stage (illumination). The concept of the creation of works contains the Aesthetic Relationship of Art with Reality that the occurrence of works of art cannot be separated from the reality that arises how the role of nature provides everything according to human needs in terms of practical life according to N. G. Chernyshevky. The creation of this painting presents representations of various things related to elements related to fishermen and the social activities of fishing communities, using the metaphor of sea fish, shrimp, crabs, squid, jellyfish, sea water, waves, sky, boat, tree roots. mangroves, baskets and others. Making the final project using ballpoint media and acrylic paint on canvas with sweeping techniques, shading techniques, blocking techniques and splashing techniques. The process of visualizing the work goes through several stages, starting from the stage of making the background on the canvas, making sketches of the main object and supporting objects, coloring objects with blocking and dusel, detailing objects using a small brush, contouring using ballpoints and the final stage of coating varnish on the canvas. Paint. This Final Project presents eight works of art that outline the problems faced by fishermen.